Eksplorasi Faktor Psikososial Yang Mempengaruhi Penyebab Konflik Siswa Di Lembaga Pendidikan Era Pasca Pandemi - Hilda Yulianti; Salsa Bila Umami; Muhammad Fathoni; Mu'alimin Mu'alimin (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
The COVID-19 pandemic has transformed the educational landscape, and this literature review aims to identify the key factors contributing to increased conflicts among students. In this analysis, it was found that social isolation, anxiety, and stress are significant psychosocial factors influencing the sources, symptoms, and causes of student conflicts. Social isolation resulting from distance learning and social restrictions plays a role in escalating interpersonal tension. Anxiety arising from pandemic-related uncertainties also contributes to conflicts among students and educators. Stress, whether caused by the pandemic itself or changes in education, has potentially negative impacts that can trigger conflicts. This article also identifies symptoms indicating student conflicts, such as a decline in the quality of social relationships, behavioral problems, and decreased academic performance. Understanding these psychosocial factors can help educational institutions develop more effective intervention strategies to address student conflicts. A deeper understanding of these issues provides a strong foundation for a holistic approach to managing student conflicts in the post-pandemic era, with an emphasis on students' psychosocial well-being to create a safe and inclusive educational environment.